Keindahan Sentuhan Tafsir Qusyairi Dalam Menafsirkan Syukur - Hakim, Luqmanul; Rambe, Uqbatul Khoir (Kamaya: Jurnal Ilmu Agama, 2025)
The concept of gratitude in Islamic teachings occupies an important position in shaping spiritual awareness and ethical values in the lives of the faithful, especially when examined through the perspective of Sufi interpretation. The meaning of gratitude is not limited to verbal expressions of divine gifts, but encompasses an inner dimension that reflects internal acknowledgment, expressions of praise, and the application of blessings in tangible actions. This study aims to examine how the verses of gratitude are interpreted in Tafsir al-Qusyairi, a tafsir work that highlights the isyāri approach and deepens the spiritual aspects of the Qur'an. The approach used is descriptive-qualitative through literature study, emphasizing thematic analysis of the word "gratitude" in the Qur'an based on the Sufi understanding according to al-Qusyairi. The study results indicate that according to al-Qusyairi, gratitude consists of three main dimensions: inner acknowledgment through the heart, verbal expression of praise, and the practice of blessings through behavior. In the Sufi framework, gratitude is viewed as a spiritual maqām that represents the existential closeness of a servant to their Lord, while also serving as a means of purifying the soul and surrendering to the Divine will. In addition to its transcendental aspect, gratitude also has positive social consequences, such as fostering humility, sensitivity towards others, and a spirit of solidarity. Therefore, the Sufi interpretation of the verses of gratitude not only enriches the inner approach to the Qur'an but also contributes to shaping the religious character and social ethics of Muslims in a complete and comprehensive manner.